Pembuatan JUNAS (Jus Nanas) Pereda Dismenorea - Safitri, Safitri; Hayati, Fatihatul (Jurnal Abdimas Kesehatan (JAK), 2024)
Dysmenorrhea is a condition of cramps in the lower abdomen followed by other symptoms, namely headaches, nausea, etc., which occur twenty-four hours before menstruation and can last one to two days. The prevalence of dysmenorrhea in Indonesia is 64.25% with 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. Non-pharmacological therapy is often used to treat dysmenorrhea because it is safe and easy to obtain and has no side effects, one of which is pineapple. Pineapple has benefits in overcoming dysmenorrhea because it contains the enzyme bromelain which has analgesic and anti-inflammatory effects. MAN 1 Muaro Jambi is an educational unit with an MA level located in Sungai Gelam District and in the working area of the Tangkit Health Center which is a center for pineapples. Even though it is known for its pineapple production, adolescence girls at MAN 1 Muaro Jambi have not made pineapple juice to relieve dysmenorrhea. Allegedly, the lack of skills of adolescence girls in making pineapple juice according to the right dosage because in community service activities they had previously been given pineapple fruit education to overcome dysmenorrhea with the result of increasing knowledge of adolescence girls by 61.86%. So demonstration of making JUNAS (Pineapple Juice) is the right choice that is beneficial for the health of the body, especially in helping to relieve dysmenorrhea and creating innovative products that have the opportunity to be produced commercially. s. This activity was carried out on 20 adolescence girls at MAN 1 Muaro Jambi in June 2023. The method used was demonstration through video tutorials. Participants enthusiastically watched and accessed video tutorials and were interested in trying to make their own at home. The manufacture of JUNAS can be developed into a commercial product and has a sale value.